2016
DOI: 10.1107/s1600576716012383
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion anisotropy as source for microstrain broadening of polycrystalline cementite, Fe3C

Abstract: Cementite (Fe3C) powder consisting of polycrystalline particles was investigated by synchrotron X‐ray diffraction and neutron diffraction at temperatures between 10 and 973 K. The data reveal a pronouncedly anisotropic thermal expansion of the orthorhombic unit cell as well as microstrain broadening varying considerably with temperature. Using a theory for predicting thermal‐microstress‐induced microstrain already applied in previous work to ambient‐temperature sealed‐tube X‐ray powder diffraction data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Krivoglaz has shown that strain broadening can only be caused by one dimensional linear defects [16] which are dislocations. (An exception to this case is when line broadening is caused by pure ECSs, as discussed in references [26] and [27].) With this:…”
Section: Profile Functions In the Cmwp Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…Krivoglaz has shown that strain broadening can only be caused by one dimensional linear defects [16] which are dislocations. (An exception to this case is when line broadening is caused by pure ECSs, as discussed in references [26] and [27].) With this:…”
Section: Profile Functions In the Cmwp Proceduresmentioning
confidence: 99%
“…As mentioned before, compatibility strains in polycrystalline materials can either be related to (i) strain gradients built up by GNDs [22][23][24] or to (ii) pure elastic strains below the yield point of hard precipitates or inclusions [25][26][27]. For the first case it has been shown in several works that LPA catches both GNDs and SSDs together.…”
Section: Profile Functions In the Cmwp Proceduresmentioning
confidence: 99%
See 3 more Smart Citations